Migration Infrastructure in International Student Mobility: Pattern, Form and Implementation at University of Mataram - Makhroja, Mega Nisfa; Zulkarnain, Zulkarnain; Yazid Bustami , Sirwan; Estriani, Heavy Nala; Claudea, Noralia; Sohaimi, Nor Suzylah (Hasanuddin University, 2025)
This research investigates how migration infrastructure facilitates worldwide student mobility within the broad scope of higher education internationalization, together with a specific focus on Universitas Mataram, Central Eastern Indonesia. Despite the push for international education through National KPI Universities (IKU) , universities in peripheral regions often face significant architectural obstacles to access the above opportunities. Taking the notion of migration systems, the study examines the ways in which institutional arrangements, actors, and practices interact to shape student mobility experiences. By using migration infrastructure concept,Student mobility and internationalization the analysis shows that during internationalization efforts to facilitate cross-border connectivity, their results are unevenly distributed The occurrence of Universitas Mataram reveals the same constraints and the development of the building of the local educational migration nerve pathway. This study found three-part analysis: a) migration infrastructure for student mobility at University of Mataram, b) pattern and form of student mobility, c) Adaptation of internationalization of higher education by supporting migration infrastructure at University of Mataram. These discoveries add to our understanding of the ways in which periphera.l higher education institutions are able to negotiate national mandates and local difficulties to participate equally at global level.